Perpetuation of the latino stereotype inatino writing : analysis of dreaming in Cuban by Cristina García and how the García girls lost their accents by Julia Alvarez - Zitterkopf, Matías (2016)
The aim of this thesis is to study and show the effects of the overuse of the Latino stereotypes in Latino literature, which we believe does not deconstruct old conceptions and images but perpetuate them. The subjects of this analysis are two literary works read during the course of studies: Dreaming in Cuban by Cristina García and How the García Girls lost their Accents by Julia Alvarez. These books helped us exemplify and support our ideas regarding the perpetuation of stereotypes since they use the common places of Latin America and the traits of its peoples. Having supported the theory with examples of the literary works chosen and having also included a chapter on stereotypes in films and the media, it was concluded that in some cases the use of old images of Latinos imposed by colonizers serve only as a colorful detail in Latino writing but do nothing to deconstruct negative stereotypes.